Adaptive enhancement design of non-significant regions of a Wushu action 3D image based on the symmetric difference algorithm - Chao Zhao; Bing Li; KaiYuan Guo (Mathematical Biosciences and Engineering, 2023)
The recognition of martial arts movements with the aid of computers has become crucial because of the vigorous promotion of martial arts education in schools in China to support the national essence and the inclusion of martial arts as a physical education test item in the secondary school examination in Shanghai. In this paper, the fundamentals of background difference algorithms are examined and a systematic analysis of the benefits and drawbacks of various background difference algorithms is presented. Background difference algorithm solutions are proposed for a number of common, challenging problems. The empty background is then automatically extracted using a symmetric disparity approach that is proposed for the initialization of background disparity in three-dimensional (3D) photos of martial arts action. It is possible to swiftly remove and manipulate the background, even in intricate martial arts action recognition scenarios. According to the experimental findings, the algorithm's optimized model significantly enhances the foreground segmentation effect of the backdrop disparity in 3D photos of martial arts action. The use of features such as texture probability is coupled to considerably enhance the shadow elimination effect for the shadow problem of background differences.